Interpreting the role of the striatum during multiple phases of motor learning. (24th May 2021) - Cataldi, Stefano; Stanley, Adrien T.; Miniaci, Maria Concetta; Sulzer, David
Abstract : The synaptic pathways in the striatum are central to basal ganglia functions including motor control, learning and organization, action selection, acquisition of motor skills, cognitive function, and emotion. Here, we review the role of the striatum and its connections in motor learning and performance. The development of new techniques to record neuronal activity and animal models of motor disorders using neurotoxin, pharmacological, and genetic manipulations are revealing pathways that underlie motor performance and motor learning, as well as how they are altered by pathophysiological mechanisms. We discuss approaches that can be used to analyze complex motor skills, particularly in rodents, and identify specific questions central to understanding how striatal circuits mediate motor learning. Abstract : Motor learning requires transitions between four phases. The first phase involves random actions driven by motivation. The second phase involves insightful behavior, when a subject links a motor action with a goal and begins to repeat the action. In the third phase, motor activity is optimized. In the fourth phase, the goal‐directed action becomes a skill or a habit, and activity shifts from dorsomedial to dorsolateral striatum.